The effect of herbivory on Deschampsia antarctica from two different geographical region - Asadnejad, Parinaz (My University, 2024)
This thesis investigates the effect of herbivory on Deschampsia antarctica, a grass species found in two geographically distinct regions: the Antarctic peninsula and Patagonia, South America. This study aims to understand how these different populations from 2 different regions respond to herbivores. Global warming causes the species shift polewards and occupy new habitats. Climate change and human activity has notably affected Antarctica and there is a possible introduction of invasive herbivore species in this region, which has been empty of any herbivores until now. In this experiment growth rates (tiller number and dry mass) and aphid numbers were used to assess the susceptibility of plants to herbivores, particularly the aphid Rhopalosiphum padi. Statistical analyses suggest significant differences in plant responses between the two regions. Patagonian plants exhibited significantly fewer aphids on them than Antarctic plants. The plant growth (dry mass) was not effected significantly by herbivores, and the plants had more tillers in the beginning, weighed more than other plants with less tillers. The variation in defense mechanisms between these geographical groups likely stems from genetic diversity in genes responsible for defense responses, since Patagonian populations were more exposed to herbivores, they have evolved a stronger mechanism to cope with insect herbivores. It is also possible that the underlying cause is the defense induction, since Patagonian plants had long term herbivore exposure during their lifetime. This study suggests that Antarctic populations of D. antarctica are more susceptible to herbivores than the Patagonian populations. This findings raise concerns around protecting Antarctica and mitigating effects of global warming since climate change might alter the species distribution and threaten the wildlife there.
Keywords: Deschampsia antarctica, Antarctic grass, herbivory, insect herbivores, biodiversity, invasive species, climate change, plant defense mechanism